39.9k views
0 votes
7(x - 3) + 3(4 - x) = -8

2 Answers

6 votes

Answer:

X=0.25

Explanation:

You use the distributive property:

7 distributed into (x - 3) and the 3 into the (4 - x).

Then you solve:

7 · x - 7 · (-3) + 3 · 4 - 3 · (- x) = - 8

7x - 21 + 12 - 3x = - 8

Then you combine/add - 21 and 12:

7x - 9 - 3x = - 8

Then you combine/add 7x and - 3x:

- 9 + 4x = - 8

Then you add the opposite of - 9 (also known as 9) to both sides of the equation:

Then it gives you 4x = 1:

Then you divide both sides by 4:

4x/4 = 1/4

Then that would give you your answer which is 0.25.

If you would like to check you would simply do the following:

First input 0.25 into where x is:

7(0.25 - 3) + 3(4 - 0.25) = - 8

Then you solve what's in the parenthesis which gives you:

7(- 2.75) + 3 (3.75) = - 8

Then you multiply 7 by what is in the parenthesis next to it and multiply 3 by the parenthesis next to it which gives you:

- 19.25 + 11.25 = - 8

Then you add - 19.25 and 11.25 which gives you:

- 8 = - 8

That means that it is correct! :)

Hope this helps! :D

User Nikhil Kumar K
by
5.4k points
2 votes

Answer:

1/4

Explanation:

7x-21+12-3x=-8

4x-9=-8

4x=1

x=1/4

User Egarc
by
4.8k points